Junior officers behavioural competency evaluation implementation: case study in the Malaysian Army infantry - Muhammad Hazim, Abdul Ghalib (2021)
Due to the lack of understanding on measuring Behavioural Competency for Junior Officers in the Malaysian Army, it shows a significant lack of performance. It is the biggest contributor to the Armed Forces, especially the Army leadership at the lowest level of command function. As this emergence took place, it is crucial for the related stakeholders such as the government, Civil Servants Department of Malaysia, and policymakers to identify necessary steps to implement Behavioural Competency in the Malaysian Army. In this context, the Junior Officers in the Malaysian Army need to participate in any leadership and performance-enhancing program and activities. It is essential to understand the factors that influence the contribution to competencies among Junior Officers in the Malaysian Army. The main objective of this study is to find gaps in implementing and evaluating the Behavioural Competency for Junior Officers in the Malaysian Army. This study has identified six respondents for interview sessions working at various departments in the Malaysian Armed Forces and have experience as immediate superiors for Junior Officers in the Malaysian Army as Officer Commandings. Findings of the research have revealed the factor of the issue and pointed recommendations for any related stakeholders and future research